The Rise of Digital Marketing Agencies: Transforming Digital Business Trends - Chairani Putri Pratiwi; Rizka Astari Rahmatika; Rafki Chandra Wibawa; Lorio Purnomo; Hasna Larasati; Siti Jahroh; Fadhilla Izzaty Syaukat (School of Business, Bogor Agricultural University (SB-IPB), 2024)
In recent years, Indonesia has emerged as a powerhouse in the digital economy, aiming to become the leading force in South East Asia. In this digital era, the promotion of products and services has become a fundamental factor for businesses, largely attributed to the advent of digital marketing. The primary objectives of this study are to explore the reliance of digital marketing agencies on digital marketing and assess the success rate of this strategy, particularly during the COVID-19 pandemic, which has significantly increased productivity and sales. Additionally, the study aims to evaluate the effectiveness of digital marketing strategies for business sustainability and discuss future trends. To shed light on this phenomenon, this study employs qualitative methods, including interviews and observations, to collect data. Various analysis techniques such as EFE, IFE, CPM, IE, SWOT, and QSPM are employed. Based on the findings, this research demonstrates that digital marketing strategies have proven highly effective, particularly in terms of the promotional and advertising techniques employed. Based on the findings, SKI Digital Marketing's strategic focus on Instagram as its primary marketing platform, coupled with a commitment to content marketing, reflects a purposeful approach to engaging a broad audience and enhancing brand visibility. The adoption of a market penetration strategy underscores the agency's determination to thrive amid intense competition. Keywords: business strategy, digital business, digital communication, digital economy, digital marketing